Influence of Prior Use of the Same or Different Effectors in a Reaching Action. Issue 1 (February 2014) - Gálvez-García, Germán; Gabaude, Catherine; de la Rosa, Francisco David; Gomez, Emilio
Use of different effectors in two consecutive actions could generate an attentional shift between the effectors with shorter latencies in the second action of reaching. 18 participants (10 men; M age = 21.3 yr.) participated in an experiment with two main variables: (1) effector switching with two levels (Switching and No Switching), where the participants use or do not use a different motor effector for each action; (2) lifting muscles, i.e., the muscles involved in the first phase of the reaching, with two levels (finger-lifting muscle and palm-lifting muscle). Premotor time, Motor time, Reaction time, Movement time, and Total time were measured. For Premotor, Movement, and Total times, faster responses were observed when there was no switching of the effector. This delay could be due to an attentional shift between motor effectors and its relations with motor processes. Possible applications include the ergonomic design of device controls, considering that the use of the same effector is beneficial when fast reaction times are sought.